Balık Yağı / Omega Yağları - Majidova, Nargiz (Kanser Hastalarının Başvurduğu Geleneksel ve Tamamlayıcı Tedaviler - Tıbbi Onkolog Gözü ile Bakış ve Onkolojik İlaçlarla Etkileşim, 2024)
İmmunonütrisyon olarak bilinen glutamin, arjinin, omega-3 yağ asitleri ve diğer substrastlar insan sağlığı için önemlidir. Bu maddeler inflamatuar yanıtı, bağırsak sistemi ve immun foknsiyonları düzenlemektedir. İmmun yanit diğer hastalıklarda olduğu gibi kanserle savaşta da önemli yer almaktadır. İmmun sistemi güçlendirerek regüle edilmesi kanser hastalıklarında da tedavinin ek parçasıdır. Birçok hastalıkta (travma, yanık, inflamatuar hastalıklar) farklı randomize kontrollü çalışma yapılsa da, kanser hastalıklarında güçlü veriler henüz azdır. Bu yazıda amacımız kanser ile balık yağı ilişkisini araştırmaktır. Glutamate, arginine, omega-3 fatty acids, and other substrates are crucial for human health and are referred to as immunonutrition. These substances regulate inflammatory enemy, gastrointestinal system and immune functions. Immune response plays an important role in the fight against cancer, as in other disease. It is an additional unit of organs in cancer cells to regulate the immune system by strengthening it. t cancer. In cancer cells, the immune system is controlled by an extra organ system that is strengthened. Although different randomized controlled studies have been conducted in many diseases (trauma, burns, inflammatory diseases), strong datas are not yet available in cancer. Our aim in this article is to investigate the relationship between cancer and fish oil.